Organizational Ambidexterity and Its Performance Implication of Foreign Ventures in an Emerging Market. Issue 5 (20th October 2022) - Ju, Min
Abstract: Exploration and exploitation are key innovation strategies of foreign ventures operating in emerging markets. In this study, we focus on organizational ambidexterity, the simultaneous pursuit of exploration and exploitation, and examine the effects of the combined and balance dimensions of ambidexterity on performance in emerging markets. We further investigate which dimension, the combined or balance, foreign ventures should adopt with different levels of marketing capability and strategic flexibility. Using a survey of foreign ventures operating in manufacturing industries in China, we find that both dimensions of organizational ambidexterity have no direct effects on performance. However, marketing capability and strategic flexibility moderate the organizational ambidexterity–firm performance relationship. The combined dimension can foster performance when foreign ventures have high levels of marketing capability and strategic flexibility. Interestingly, the balance dimension of organizational ambidexterity profitably contributes to performance when foreign ventures possess low levels of marketing capability and strategic flexibility.